Zinc-Modified Nanotransporter of Doxorubicin for Targeted Prostate Cancer Delivery - Skalickova, Sylvie; Loffelmann, Martin; Gargulak, Michael; Kepinska, Marta; Docekalova, Michaela; Uhlirova, Dagmar; Stankova, Martina; Fernandez, Carlos; Milnerowicz, Halina; Ruttkay-Nedecky, Branislav; Kizek, Rene (Nanomaterials (Basel, Switzerland), 2017)
This work investigated the preparation of chitosan nanoparticles used as carriers for doxorubicin for targeted cancer delivery. Prepared nanocarriers were stabilized and functionalized via zinc ions incorporated into the chitosan nanoparticle backbone. We took the advantage of high expression of sarcosine in the prostate cancer cells. The prostate cancer targeting was mediated by the AntiSar antibodies decorated surface of the nanocage. Formation of the chitosan nanoparticles was determined using a ninhydrin assay and differential pulse voltammetry. Obtained results showed the strong effect of tripolyphosphine on the nanoparticle formation. The zinc ions affected strong chitosan backbone coiling both in inner and outer chitosan nanoparticle structure. Zinc electrochemical signal depended on the level of the complex formation and the potential shift from -960 to -950 mV. Formed complex is suitable for doxorubicin delivery. It was observed the 20% entrapment efficiency of doxorubicin and strong dependence of drug release after 120 min in the blood environment. The functionality of the designed nanotransporter was proven. The purposed determination showed linear dependence in the concentration range of Anti-sarcosine IgG labeled gold nanoparticles from 0 to 1000 µg/mL and the regression equation was found to be y = 3.8x - 66.7 and R² = 0.99. Performed ELISA confirmed the ability of Anti-sarcosine IgG labeled chitosan nanoparticles with loaded doxorubicin to bind to the sarcosine molecule. Observed hemolytic activity of the nanotransporter was 40%. Inhibition activity of our proposed nanotransporter was evaluated to be 0% on the experimental model of S. cerevisiae. Anti-sarcosine IgG labeled chitosan nanoparticles, with loaded doxorubicin stabilized by Zn ions, are a perspective type of nanocarrier for targeted drug therapy managed by specific interaction with sarcosine and metallothionein for prostate cancer.
Keywords: chitosan; prostate cancer; doxorubicin; ninhydrin; peroxidase activity; gold nanoparticle; sarcosine; magnetic gold nanoparticle; zinc